3. MORFOLOGI DAN KANDUNGAN KARBOHIDRAT KELENJAR LINGUALIS DAN SUBLINGUALIS ITIK (Anas plathyrinchos) (Morphology and Carbohydrates Content in Lingual and Sublingual Glands of Duck (Anas plathyrinchos)) - M Jalaluddin (Jurnal Medika Veterinaria, 2016)
This study was aimed to find out the morphology and carbohydrates content of lingual and sub-lingual glands of duck (Anas plathyrinchos). Sample used in this study was lingual and sublingual glands of a one year old female duck. Anatomy morphology and histology of lingual and sublingual glands were observed after processed into histological preparation and stained with hematoxylin-eosin (HE) then stained further with alcian blue (AB) pH 2.5 and periodic acid Schiff (PAS) to detect carbohydrate contents. The results showed that the lingual gland of duck cannot be observed due to its location below the epithelial layer of the tongue. While the sublingual gland of duck has an elongated shape and not granulated like typically glands, located at ventral tongue (dorsoventral lingual) between os mandibulae and covered with musculus digastricus venter oral. Staining with AB pH 2.5 and PAS showed that cytoplasm of secretory cell and secrete of lingual and sublingual glands contain acidic and neutral carbohydrates which indicated a positive reaction with intensity ranging from weak (+) to strong (+++). This study concluded that the lingual and sublingual gland found in female duck is a complex tubular gland with mucous secretory cells type. ____________________________________________________________________________________________________________________